Effect of Acetyl tributyl citrate on bone metabolism based on network toxicology and molecular docking technology - Xuan Lin; Kun Lin; Yue Lai; Qingping Peng; Miao Xu; Yiting Xu; Jialin Yang; Huan Liu; Jianlin Shen (Ecotoxicology and Environmental Safety)
This study aims to elucidate the intricate effects of Acetyl tributyl citrate (ATBC) on bone metabolism, disentangling the underlying molecular mechanisms that govern the impact of environmental contaminants on disease processes. Leveraging the exhaustive exploration of databases such as ChEMBL, STITCH, GeneCards, and OMIM, we have identified a comprehensive list of 164 potential targets intimately associated with both ATBC and bone metabolism. Following rigorous refinement using the STRING platform and Cytoscape software, we pinpointed ten core targets, encompassing KDM1A, EP300, HDAC2, EHMT2, DNMT1, and several others. In-depth Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses, conducted within the Metascape database, revealed that the core targets of ATBC’s influence on bone metabolism are predominantly concentrated within vital signaling cascades, including thyroid hormone signaling, FOXO signaling, glucagon signaling, AMPK signaling, insulin signaling, adipocytokine signaling, and Notch signaling pathways. Additionally, molecular docking simulations performed with AutoDock software confirmed the robust binding interactions between ATBC and these core targets, reinforcing our understanding of their interactions. To explore the cellular impact of ATBC, we performed in vitro experiments using osteoblasts (MC3T3-E1) exposed to relevant concentrations. Our findings revealed that low-dose ATBC (100 μM) significantly impaired cell proliferation and migration. Concurrently, we observed a downregulation in the transcriptional expression of key epigenetic regulators (KDM1A, EP300, HDAC2), suggesting that ATBC can disrupt bone metabolism at the cellular level. Collectively, our findings provide a theoretical scaffold for comprehending the intricate molecular mechanisms mediating ATBC’s effects on bone metabolism, and paves the way for the development of preventive and therapeutic strategies against orthopedic disorders that may arise from exposure to plastic products containing ATBC or excessive ATBC environments.